FGF23 Actions in CKD-MBD and other Organs During CKD - Sun, Ting; Yu, Xijie (Current Medicinal Chemistry, 2023)
Fibroblast growth factor 23 (FGF23) is a new endocrine product discovered in the past decade. In addition to being related to bone diseases, it has also been found to be related to kidney metabolism and parathyroid metabolism, especially as a biomarker and a key factor to be used in kidney diseases. FGF23 is upregulated as early as the second and third stages of chronic kidney disease (CKD) in response to relative phosphorus overload. The early rise of FGF23 has a protective effect on the body and is essential for maintaining phosphate balance. However, with the decline in renal function, eGFR (estimated glomerular filtration rate) declines, and the phosphorus excretion effect caused by FGF23 is weakened. It eventually leads to a variety of complications, such as bone disease (Chronic Kidney Disease-Mineral and Bone Metabolism Disorder), vascular calcification (VC), and more. Monoclonal antibodies against FGF23 are currently used to treat genetic diseases with increased FGF23. CKD is also a state of increased FGF23. This article reviews the current role of FGF23 in CKD and discusses the crosstalk between various organs under CKD conditions and FGF23. Studying the effect of hyperphosphatemia on different organs of CKD is important. The prospect of FGF23 for therapy is also discussed.
Keywords: parathyroid